PO006 Encephalitis on the neuro-icu: changing patterns. (1st December 2017) - Brown, Rachel; Hirsch, Nicholas P; Radcliffe, Jeremy; Kullmann, Dimitri M; Howard, Robin S
Abstract : With the discovery of antibodies to the N-methyl-d-aspartate (NMDA) receptor, the voltage-gated potassium channel complex (VGKC), and to other neuronal targets, the investigation and management of encephalitis has changed dramatically. While the aetiology of encephalitis remains unexplained in a large proportion, a significant number are recognised to be immune-mediated and therefore potentially treatable. For many patients, acute care is provided on either a general or specialist neuro-critical care unit (NCCU). Between 2006 and 2016, 81 patients were admitted to the NCCU at Queen Square with a diagnosis of encephalitis. Within this group, patients with presumed immune-mediated encephalitis (50 patients) outweighed those with encephalitis caused by infection (31 patients). 22 had anti-NMDA antibodies and 13 had anti-VGKC antibodies. Presumed or confirmed viral encephalitis was seen in 13 patients, and in 18 patients the cause was either unspecified or related to another organism. This study reviews our experience of managing encephalitis on the NCCU over the last 11 years. It is unclear why patients with autoimmune encephalitis seem over-represented in our patient population. Relative confidence in managing viral encephalitis among general medical/ICU teams may play a part, with more atypical cases sparking referral to a specialist unit for diagnosis and further management.